Enhancing Talent Retention Through AI-Driven Employer Branding: The Mediating Role of Recruitment Marketing and The Moderating Effect of AI-Powered Personalization - Safroni Isrososiawan; Muhammad Azizurrohman; Risky Angga Pramuja (STI Policy and Management Journal, 2025)
The adoption of artificial intelligence (AI) in human resource management is transforming employer branding, recruitment marketing, and talent retention. This study examines how AI-driven employer branding enhances recruitment marketing effectiveness and improves retention, considering the roles of technological readiness, organizational culture, and strategic HR practices. Using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with data from 312 HR professionals and employees across Indonesia, Taiwan, Malaysia, Singapore, the United States, the United Kingdom, and Germany, the findings confirm that AI-driven employer branding positively influences recruitment marketing and retention. The mediation analysis reveals that recruitment marketing partially mediates this relationship, while the moderation analysis shows that AI-powered personalization strengthens the impact of recruitment marketing on retention. These findings highlight the need for organizations to strategically integrate AI in employer branding and recruitment to improve hiring outcomes. This study advances theoretical insights into AI adoption in HRM by demonstrating its influence on branding strategies. From a managerial perspective, the results emphasize the importance of balancing AI automation with human interaction. Despite its cross-sectional limitations, future research should explore longitudinal impacts and ethical considerations in AI-driven recruitment. Organizations must adopt personalized, data-driven AI solutions to enhance employer branding and retention in the evolving job market